2007
DOI: 10.1007/s00420-007-0281-1
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous abortions in female populations occupationally exposed to ionizing radiation

Abstract: For exposure levels within standard recommended guidelines, radioisotopes are far more likely to play a role in the occurrence of spontaneous abortions than X-rays. Such biological effect is not detectable by deviations in CA frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Health care workers, dental assistants, and veterinarians can be exposed via X-rays, CT scans, fluoroscopies, radioactive isotopes, and radioactive implants; these are listed in order of increasing relative biological effectiveness. A recent study found a 3-fold higher spontaneous abortion rate among women occupationally exposed to radioisotopes compared to X-rays, 38 suggesting a dose-response relationship. In addition, staff who use mobile X-ray machines may find it difficult to follow guidelines to reduce exposure.…”
Section: Commentmentioning
confidence: 98%
“…Health care workers, dental assistants, and veterinarians can be exposed via X-rays, CT scans, fluoroscopies, radioactive isotopes, and radioactive implants; these are listed in order of increasing relative biological effectiveness. A recent study found a 3-fold higher spontaneous abortion rate among women occupationally exposed to radioisotopes compared to X-rays, 38 suggesting a dose-response relationship. In addition, staff who use mobile X-ray machines may find it difficult to follow guidelines to reduce exposure.…”
Section: Commentmentioning
confidence: 98%
“…11 It has been reported that chronic occupational exposure to radioactive isotopes is associated with a significantly greater risk of miscarriage than exposure to diagnostic radiographs. 12 This may be due to the degree of ionizing radiation and the potential toxicity of the metal and halogen components used to generate these isotopes. 12 On the basis of the sum of these data, hospital employees who are appropriately shielded during the administration of radiologic studies should not have increased reproductive risks.…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…12 This may be due to the degree of ionizing radiation and the potential toxicity of the metal and halogen components used to generate these isotopes. 12 On the basis of the sum of these data, hospital employees who are appropriately shielded during the administration of radiologic studies should not have increased reproductive risks. Those who are regularly involved in studies that require fluoroscopy should have levels of radiation exposure monitored to ensure exposure does not exceed recommended doses 10 and those that handle radioisotopes should limit exposure.…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…Although pregnant women are usually isolated from jobs which could jeopardise normal development of the foetus, the fi rst trimester of pregnancy can go unnoticed, and the foetus may be exposed to increased risk. In hospitals where women are occupationally exposed to radioisotopes (iodine, chromium, thallium, technetium, thorium) the miscarriage incidence is signifi cantly higher than in women occupationally exposed to X-rays (36). It seems that health effects of radioisotopes applied in diagnostics are not limited to their own radioactivity but may also be owed to contamination with lead, tin, or nickel due to the technology of production, which act as heavy metals or xenoestrogens (36).…”
Section: Ionising Radiationmentioning
confidence: 99%
“…Several studies of child exposure to chemical agents used the following biomarkers: DNA, haemoglobin and protein adducts, comet assay, and gene mutation assay (31)(32)(33)(34)(35). They suggest specifi c susceptibility of the foetus and child and call for further search for the most sensitive methods for certain types of environmental (radio)chemicals (30,36).…”
mentioning
confidence: 99%